The Role of Social Cognitive Theory in Farm‐to‐School‐Related Activities: Implications for Child Nutrition1. (8th July 2013) - Berlin, Linda; Norris, Kimberly; Kolodinsky, Jane; Nelson, Abbie
ABSTRACT: BACKGROUND: Farm‐to‐school (FTS) programs are gaining attention for many reasons, one of which is the recognition that they could help stem the increase in childhood overweight and obesity. Most FTS programs that have been evaluated have increased students' selection or intake of fruits and vegetables following the incorporation of FTS components. However, the wide range of activities that are typically part of FTS programs make it difficult to pinpoint which components have the greatest potential to improve students' health behaviors. Within the field of nutrition education, theory‐based interventions that target the key underlying factors influencing health behavior offer the most promise. METHODS: We review existing research on dietary health impacts and implications of 3 key FTS‐related activities and explore the component activities of FTS in terms of their potential to address the key constructs of social cognitive theory (SCT)—which is a current best practice in the field of nutrition—suggesting that FTS programs incorporating a diverse set of activities appear to be most promising. RESULTS: We find that components of FTS programs incorporate many of the key theoretical constructs in SCT, and show that FTS programs have great potential to facilitate movement toward desired dietary changes. However, it is unlikely that a set of activities in any one current FTS program addresses multiple constructs of the theory in a systematic manner. CONCLUSION: More intentional inclusion of diverse activities would likely be beneficial. Future research can test these assertions.